Barium-doped lanthanum cobaltate perovskite catalyst and preparation method and application thereof

By doping barium at the A-position of the lanthanum cobaltate perovskite catalyst, a barium-doped lanthanum cobaltate perovskite catalyst was prepared, which solved the problem of insufficient catalytic activity of existing perovskite oxides, and achieved the effect of efficient catalytic ozone degradation of organic pollutants.

CN119500158APending Publication Date: 2025-02-25HANGZHOU CHENGJIE ENVIRONMENTAL PROTECTION
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411607368.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing perovskite oxides are less used in catalytic ozone oxidation, and the types and properties of catalysts are diversified, resulting in less development of high-performance perovskite catalysts and the catalytic activity needs to be further improved.

Method used

By doping barium at the A-position of the lanthanum cobaltate perovskite catalyst, a barium-doped lanthanum cobaltate perovskite catalyst (La1-xBaxCoO3) was prepared to increase the oxygen vacancy and oxygen mobility, thereby improving the ability of catalyzed ozone to produce free radicals.

Benefits of technology

It significantly improves the efficiency of the catalyst in catalyzing ozone to degrade organic pollutants, has high catalytic activity, is cheap raw materials, is simple in preparation, and can efficiently catalyze the degradation of wastewater containing organic pollutants without secondary pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119500158A_ABST
    Figure CN119500158A_ABST
Patent Text Reader

Abstract

The invention discloses a barium-doped lanthanum cobaltate type perovskite catalyst and a preparation method thereof, the molecular formula of the barium-doped lanthanum cobaltate type perovskite catalyst is La1-xBaxCoO3, wherein 0 lt; and x is less than or equal to 0.5. The invention also discloses an application of the barium-doped lanthanum cobaltate perovskite catalyst in catalyzing ozone to degrade organic pollutants. According to the barium-doped lanthanum cobaltate type perovskite catalyst, barium is doped at the A site of perovskite, more oxygen vacancies and higher oxygen mobility are achieved, ozone can be catalyzed to generate more free radicals, and therefore degradation of organic pollutants is accelerated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of water treatment, and in particular to a barium-doped lanthanum cobaltate type perovskite catalyst and a preparation method and application thereof. Background Art

[0002] With the rapid development of society, a large amount of industrial wastewater and domestic sewage has been generated, and these sewage cannot be properly treated in time, causing rivers, groundwater, etc. to be polluted to varying degrees. Such an ecological environment seriously threatens and restricts the sustainable development of mankind, so it is urgent to take effective measures to treat wastewater.

[0003] Acetic acid (AcOH) is a common colorless liquid that is widely used in the manufacture of plastics, chemicals, esters, dyes and other industrial fields. In addition, acetic acid is also the end product of the chemical oxidation process to degrade organic matter. When acetic acid is discharged into the water in large quantities, it will lower the pH value of the water, increase the organic matter content, and lead to eutrophication of the water, thereby causing algae, zooplankton and other organisms in the water to reproduce in large numbers, causing water quality to deteriorate. In addition, as people become more and more dependent on antibiotics, the increasing amount of antibiotics in wastewater has also become a major environmental problem. Thiamphenicol (TAP) is an antibiotic that, although it has strong antibacterial properties, is potentially dangerous to the safety of humans, animals and plants. TAP can be excreted into the environment after metabolism by humans and animals, causing water pollution.

[0004] Ozone is widely used in the deep treatment of drinking water and sewage because of its good disinfection, degradation of macromolecular organic matter and deodorization capabilities. Heterogeneous catalytic ozone oxidation technology is an economical and efficient advanced oxidation technology for water treatment, and is one of the new technologies for enhancing ozone oxidation to remove highly stable organic pollutants in water. It is characterized by the production of highly oxidizing and non-selective hydroxyl radicals (·OH), which completely mineralize and convert organic pollutants into carbon dioxide and water. The emergence of this advanced oxidation technology provides a new method for the treatment of many pollutants in water. Heterogeneous catalytic ozone oxidation technology uses catalysts such as metal oxides, metals or metal oxides loaded on carriers, activated carbon and hollow microporous materials, etc., to promote ozone decomposition to produce more ·OH to degrade organic pollutants, and heterogeneous catalytic ozone oxidation technology overcomes some problems of traditional ozone oxidation technology, such as low ozone yield and low utilization rate, and the oxidation activity of ozone has a certain selectivity.

[0005] Perovskite is a rich and relatively cheap mineral with a general structural formula of ABO. 3, where A is generally a rare earth cation and B is generally a transition metal cation. Perovskite has shown high catalytic oxidation activity in heterogeneous catalytic ozone oxidation technology, and can achieve enhanced degradation of organic pollutants in water. The catalytic effect of perovskite depends on the transition metal ion at the B position. The variable valence characteristics of the B-position element and its multivalent state mutual conversion, as well as the lattice oxygen defects in the structure can promote ozone decomposition to produce more active oxygen free radicals, thereby achieving rapid and efficient degradation of pollutants. Therefore, the improvement of perovskite catalysts in the prior art is generally to dope the B position, and the catalytic activity needs to be further improved.

[0006] However, the application of perovskite oxides in catalytic ozone oxidation is still rare, and the types and properties of catalysts are diverse. In recent years, relatively few high-performance perovskite catalysts have been developed. Therefore, further research is needed to advance and apply perovskite oxide catalytic ozone oxidation technology. Summary of the invention

[0007] The invention provides a barium-doped lanthanum cobaltate type perovskite catalyst and a preparation method thereof, which greatly improves the efficiency of the lanthanum cobaltate type perovskite catalyst in catalyzing ozone degradation of organic pollutants.

[0008] The technical solution of the present invention is as follows:

[0009] A barium-doped lanthanum cobaltate perovskite catalyst, the molecular formula of which is La 1-x Ba x CoO 3 , where 0 <x≤0.5。

[0010] The barium-doped lanthanum cobaltate perovskite catalyst of the present invention is doped with barium at the A position of the perovskite, has more oxygen vacancies and higher oxygen mobility, can catalyze ozone to produce more free radicals, and thus accelerates the degradation of organic pollutants.

[0011] The present invention also provides a method for preparing the barium-doped lanthanum cobaltate perovskite catalyst, comprising the following steps:

[0012] (1) adding citric acid to the precursor salt solution, adjusting the pH value of the solution to 7-9 with aqueous ammonia, evaporating the solvent, and obtaining a jelly;

[0013] The precursor salt solution is lanthanum salt, barium salt and cobalt salt. In the precursor salt solution, the molar ratio of lanthanum element, barium element and cobalt element is 0.1-0.5:0.1-0.5:1;

[0014] (2) drying and grinding the colloid to obtain a powder;

[0015] (3) The powder is heated to 550-750° C. at a rate of 2-8° C. / min and calcined for 4-5 hours to obtain a barium-doped lanthanum cobaltate perovskite catalyst.

[0016] The lanthanum salt, barium salt and cobalt salt are soluble lanthanum salt, barium salt and cobalt salt.

[0017] Preferably, the heating rate in step (3) is 4-6°C / min. Too fast a heating rate will result in poor crystallinity of the catalyst and affect the catalytic performance of the catalyst.

[0018] Preferably, the calcination temperature in step (3) is 600-700°C.

[0019] The present invention also provides the use of the barium-doped lanthanum cobaltate perovskite catalyst in catalyzing ozone degradation of organic pollutants.

[0020] The applications described include:

[0021] The barium-doped lanthanum cobaltate perovskite catalyst is added into wastewater containing organic pollutants; and ozone is introduced into the wastewater to carry out catalytic oxidation reaction.

[0022] Preferably, the mass volume ratio of the barium-doped lanthanum cobaltate perovskite catalyst to wastewater is (0.04-0.08) g:250 mL.

[0023] Preferably, the initial pH value of the wastewater is 5-9.

[0024] Preferably, the dosage of ozone is 2-30 mg / min.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] (1) With LaCoO 3 Compared with the catalyst, the barium-doped lanthanum cobaltate perovskite catalyst of the present invention is a novel La 1-x Ba x CoO 3 The catalyst has more oxygen vacancies and higher oxygen mobility, and can catalyze ozone to produce more free radicals, thereby accelerating the degradation of organic pollutants.

[0027] (2) Synthesis of novel La by the present invention 1-x Ba x CoO 3 The catalyst has high catalytic activity, cheap raw materials, and simple preparation method. It can efficiently catalyze the degradation of wastewater containing organic pollutants without causing secondary pollution. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1It is the XRD spectra of the catalysts prepared in Example 2 and Comparative Example 1.

[0029] Figure 2 The degradation effects of the barium-doped lanthanum cobaltate perovskite catalysts of Examples 1 to 3, the catalysts of Comparative Examples 1 to 4, and ozone alone on acetic acid in the absence of a catalyst are shown.

[0030] Figure 3 The degradation effects of the barium-doped lanthanum cobaltate perovskite catalyst of Example 2, the catalyst of Comparative Example 1, and ozone alone in the absence of a catalyst on thiamphenicol are shown.

[0031] Figure 4 This is the degradation effect of the barium-doped lanthanum cobaltate perovskite catalyst of Example 2 on acetic acid under different pH conditions. DETAILED DESCRIPTION

[0032] The present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be pointed out that the embodiments described below are intended to facilitate the understanding of the present invention and do not have any limiting effect on the present invention.

[0033] Example 1

[0034] The preparation method of the barium-doped lanthanum cobaltate perovskite catalyst comprises:

[0035] 8mmoL La(NO 3 ) 3 6H 2 O, 2mmoL Ba(NO 3 ) 2 , 10mmoL Co(NO 3 ) 2 6H 2 O, uniformly dispersed in 100 mL of deionized water, then 30 mmol of citric acid was added to dissolve, the solution pH was adjusted to 8 with ammonia water, stirred at 80 ° C until the solvent evaporated, the obtained gel was dried at 120 ° C for 12 h, the dried sample was taken out and ground into powder with a mortar, and the powdered product was placed in a muffle furnace and calcined at 650 ° C for 4 h to obtain a barium-doped lanthanum cobalt oxide perovskite catalyst, marked as La 0.8 Ba 0.2 CoO 3 .

[0036] Example 2

[0037] The preparation method of the barium-doped lanthanum cobaltate perovskite catalyst comprises:

[0038] 6mmoL La(NO 3 ) 3 6H 2 O,4mmoL Ba(NO3 ) 2 , 10mmoL Co(NO 3 ) 2 6H 2 O, uniformly dispersed in 100 mL of deionized water, then 30 mmol of citric acid was added to dissolve, the solution pH was adjusted to 8 with ammonia water, stirred at 80 ° C until the solvent evaporated, the obtained gel was dried at 120 ° C for 12 h, the dried sample was taken out and ground into powder with a mortar, and the powdered product was placed in a muffle furnace and calcined at 650 ° C for 4 h to obtain a barium-doped lanthanum cobalt oxide perovskite catalyst, marked as La 0.6 Ba 0.4 CoO 3 .

[0039] Example 3

[0040] The preparation method of the barium-doped lanthanum cobaltate perovskite catalyst comprises:

[0041] 5mmoL La(NO 3 ) 3 6H 2 O, 5mmoL Ba(NO 3 ) 2 , 10mmoL Co(NO 3 ) 2 6H 2 O, uniformly dispersed in 100 mL of deionized water, then 30 mmol of citric acid was added to dissolve, the solution pH was adjusted to 8 with ammonia water, stirred at 80 ° C until the solvent evaporated, the obtained gel was dried at 120 ° C for 12 h, the dried sample was taken out and ground into powder with a mortar, and the powdered product was placed in a muffle furnace and calcined at 650 ° C for 4 h to obtain a barium-doped lanthanum cobalt oxide perovskite catalyst, marked as La 0.5 Ba 0.5 CoO 3 .

[0042] Comparative Example 1

[0043] The preparation method of the catalyst comprises:

[0044] 10mmoL La(NO 3 ) 3 6H 2 O, 10mmoLCo(NO 3 ) 2 6H 2O was evenly dispersed in 100 mL of deionized water, and then 30 mmol of citric acid was added to dissolve it. The pH of the solution was adjusted to 8 with ammonia water, and the solution was stirred at 80 ° C until the solvent evaporated. The obtained gel was dried at 120 ° C for 12 h, and the dried sample was taken out and ground into powder with a mortar. The powdered product was placed in a muffle furnace and calcined at 650 ° C for 4 h to obtain a catalyst, which was marked as LaCoO 3 .

[0045] Comparative Example 2

[0046] The preparation method of the catalyst comprises:

[0047] 10mmoL La(NO 3 ) 3 6H 2 O, 10mmoL Ba(NO 3 ) 2 , uniformly dispersed in 100 mL of deionized water, then 30 mmol of citric acid was added to dissolve, the solution pH was adjusted to 8 with ammonia water, stirred at 80 ° C until the solvent evaporated, the obtained gel was dried at 120 ° C for 12 h, the dried sample was taken out and ground into powder with a mortar, and the powdered product was placed in a muffle furnace and calcined at 650 ° C for 4 h to obtain a catalyst, marked as LaBaO 3 .

[0048] Comparative Example 3

[0049] The preparation method of the catalyst comprises:

[0050] 10mmoL La(NO 3 ) 3 6H 2 O, 4mmoL Fe(NO 3 ) 3 9H 2 O,6mmoL Co(NO 3 ) 2 6H 2 O was evenly dispersed in 100 mL of deionized water, and then 30 mmol of citric acid was added to dissolve it. The pH of the solution was adjusted to 8 with ammonia water, and the solution was stirred at 80 ° C until the solvent evaporated. The obtained gel was dried at 120 ° C for 12 h, and the dried sample was taken out and ground into powder with a mortar. The powdered product was placed in a muffle furnace and calcined at 650 ° C for 4 h to obtain a catalyst, which was marked as LaCo 0.6 Fe 0.4 O 3 .

[0051] Comparative Example 4

[0052] The preparation method of the catalyst comprises:

[0053] 10mmoL La(NO 3 ) 3 6H 2 O, 4mmoL Al(NO 3 ) 3 9H 2 O,6mmoL Co(NO 3 ) 2 6H 2 O was evenly dispersed in 100 mL of deionized water, and then 30 mmol of citric acid was added to dissolve it. The pH of the solution was adjusted to 8 with ammonia water, and the solution was stirred at 80 ° C until the solvent evaporated. The obtained gel was dried at 120 ° C for 12 h, and the dried sample was taken out and ground into powder with a mortar. The powdered product was placed in a muffle furnace and calcined at 650 ° C for 4 h to obtain a catalyst, which was marked as LaCo 0.6 Al 0.4 CoO 3 .

[0054] test

[0055] The catalysts prepared in Example 2 and Comparative Example 1 were characterized by using an intelligent multifunctional X-ray diffractometer Smartlab SE from Rigaku of Japan. The test conditions were as follows: target source Cu Kα, scanning speed of 2° / min, and scanning angle of 20-80°.

[0056] The characterization results are as follows Figure 1 As shown in the figure, it can be seen that the unmodified LaCoO 3 The sample diffraction peaks are consistent with the standard card PDF#97-020-1763, indicating that the unmodified sample presents a typical rhombic perovskite structure. When metal barium is doped at the A position, the XRD pattern shows that the main diffraction peak becomes broadened, and the double peak structure near the (-110) crystal plane is transformed into a single peak structure after doping, that is, the crystal structure is closer to the cubic crystal structure. This shows that Ba 2+ Part of it is placed inside the perovskite structure, resulting in a modification of the crystal structure. 2+ Replaces the smaller La in the perovskite structure 3+ , the main diffraction peak position (~32.84°2θ) gradually shifts to lower 2θ values.

[0057] Application Example 1

[0058] At normal temperature and pressure, catalytic ozone oxidation is carried out with a bubbling column reactor. Ozone is produced by a laboratory ozone generator (TOG C2, Ozonya Environmental Technology Co., Ltd.) using oxygen as feed gas. During the reaction, 250 mL of simulated polluted water (containing 20 mg / L of acetic acid in the polluted water) and a certain amount of catalyst (the catalyst is selected from the barium-doped lanthanum cobaltate perovskite catalyst of Example 1-3 and the catalyst of Comparative Example 1-4) are added to the reactor, and the initial pH of the solution is adjusted to 7, and the volume ratio of the catalyst dosage (the catalyst dosage is 0.05 g) to the polluted water is 0.2 g / L, and ozone is continuously introduced during continuous stirring, and the dosage of ozone is 25 mg / min. 15 mL of water sample is taken out from the reactor every 3 minutes, and the catalyst is removed by 0.45 μm microporous membrane filtration. Then 1 mL of filtrate is injected into a liquid phase vial, and the concentration of residual acetic acid in the solution is detected by high performance liquid chromatography (HPLC, Ultimate3000).

[0059] This application example studies the degradation effects of the barium-doped lanthanum cobalt oxide perovskite catalysts of Examples 1-3, the catalysts of Comparative Examples 1-4, and ozone alone on acetic acid. The results are as follows: Figure 2 As shown by Figure 2 It can be seen that the catalysts doped with different proportions of barium all showed good catalytic degradation effects on acetic acid, among which La 0.6 Ba 0.4 CoO 3 The efficiency of acetic acid degradation is the highest, and the degradation rate can reach 58% when the reaction time is 9 minutes. The removal rate of acetic acid in the solution using the catalyst of Examples 1-3 is significantly higher than that of the catalyst of the comparative example, indicating that the perovskite catalyst doped with metal barium at the A position can make ozone produce more free radicals and enhance the degradation efficiency of organic pollutants.

[0060] Application Example 2

[0061] Catalytic ozone oxidation was performed using a bubbling column reactor at room temperature and pressure. Ozone was produced by a laboratory ozone generator (TOG C2, Ozonya Environmental Technology Co., Ltd.) using oxygen as the feed gas. During the reaction, 250 mL of simulated contaminated water (containing 20 mg / L of thiamphenicol in the contaminated water) and a certain amount of catalyst (the catalyst was selected from the barium-doped lanthanum cobaltate perovskite catalyst of Example 2, the catalyst of Comparative Example 1, and the degradation effect of thiamphenicol under the condition of ozone alone were added to the reactor. The initial pH of the solution was adjusted to 7, and the volume ratio of the catalyst dosage (the catalyst dosage was 0.05 g) to the contaminated water was 0.2 g / L. During this period, constant stirring and continuous introduction of ozone were performed, and the dosage of ozone was 2 mg / min. 15 mL of water sample was taken out from the reactor every 2 minutes, and the catalyst was removed by filtration through a 0.45 um microporous membrane. Then 1 mL of the filtrate was injected into a liquid phase vial, and the concentration of residual thiamphenicol in the solution was detected by high performance liquid chromatography (HPLC, Ultimate 3000).

[0062] This application example studies the degradation effects of the barium-doped lanthanum cobaltate perovskite catalyst of Example 2 and the catalyst of Comparative Example 1 on thiamphenicol under the conditions of ozone alone. The results are as follows: Figure 3 As shown by Figure 3 It is known that the synthesized new catalyst La 0.6 Ba 0.4 CoO 3 93% of thiamphenicol can be degraded within 8 minutes. This shows again that the barium-doped lanthanum cobaltate perovskite catalyst of Example 2 has significantly enhanced catalytic activity compared to the catalyst of Comparative Example 1.

[0063] Application Example 3

[0064] At normal temperature and pressure, catalytic ozone oxidation is carried out with a bubbling column reactor. Ozone is produced by a laboratory ozone generator (TOG C2, Ozonya Environmental Technology Co., Ltd.) using oxygen as feed gas. During the reaction, 250 mL of simulated polluted water (containing 20 mg / L of acetic acid in the polluted water) and a certain amount of catalyst (the catalyst is selected from the barium-doped lanthanum cobaltate perovskite catalyst of Example 2) are added to the reactor, and the initial pH of the solution is adjusted to 5, 7, 9, respectively, and the volume ratio of the catalyst dosage (the catalyst dosage is 0.05 g) to the polluted water is 0.2 g / L, and constant stirring and continuous ozone is introduced during the period, and the dosage of ozone is 25 mg / min. 15 mL of water sample is taken out from the reactor every 3 minutes, and the catalyst is removed by 0.45 um microporous membrane filtration. Then 1 mL of filtrate is injected into a liquid phase vial, and the concentration of residual acetic acid in the solution is detected by high performance liquid chromatography (HPLC, Ultimate 3000).

[0065] The purpose of this test example is to explore the barium-doped lanthanum cobaltate perovskite catalyst (the catalyst used is the catalyst La in Example 2). 0.6 Ba 0.4 CoO 3 ) to the degradation efficiency of acetic acid in a wide pH range. Figure 4 As shown by Figure 4 It can be seen that 3 / La 0.6 Ba 0.4 CoO 3 The system can always promote ozone oxidation in the pH range of 5.0-9.0, and shows good removal effect on wastewater containing acetic acid. When the solution is alkaline (pH 9), the solution degradation efficiency is as high as 63%, because under alkaline conditions, OH - The ozone decomposition is promoted to produce more hydroxyl radicals, thereby improving the removal rate of acetic acid. The degradation efficiency is more than 50% when the solution is neutral or alkaline, indicating that the catalyst can be used in a wide pH range.

[0066] The embodiments described above provide a detailed description of the technical solutions and beneficial effects of the present invention. It should be understood that the above are only specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, supplements and equivalent substitutions made within the scope of the principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A barium-doped lanthanum cobaltate perovskite catalyst, characterized in that: Its molecular formula is La 1-x Ba x CoO3, of which 0 <x≤0.5。 2. A method for preparing the barium-doped lanthanum cobaltate perovskite catalyst according to claim 1, characterized in that: The following steps are involved: (1) adding citric acid to the precursor salt solution, adjusting the pH value of the solution to 7-9 with aqueous ammonia, evaporating the solvent, and obtaining a jelly; The precursor salt solution is lanthanum salt, barium salt and cobalt salt. In the precursor salt solution, the molar ratio of lanthanum element, barium element and cobalt element is 0.1-0.5:0.1-0.5:1; (2) drying and grinding the colloid to obtain a powder; (3) The powder is heated to 550-750° C. at a rate of 2-8° C. / min and calcined for 4-5 hours to obtain a barium-doped lanthanum cobaltate perovskite catalyst.

3. The method for preparing the barium-doped lanthanum cobaltate perovskite catalyst according to claim 1, characterized in that: The heating rate in step (3) is 4-6°C / min.

4. The method for preparing the barium-doped lanthanum cobaltate perovskite catalyst according to claim 1, characterized in that: The calcination temperature in step (3) is 600-700°C.

5. Use of the barium-doped lanthanum cobaltate perovskite catalyst according to claim 1 in catalyzing ozone degradation of organic pollutants.

6. The use according to claim 5, characterized in that: include: adding the barium-doped lanthanum cobaltate perovskite catalyst into wastewater containing organic pollutants; Ozone is introduced into the wastewater to carry out catalytic oxidation reaction.

7. The use according to claim 5, characterized in that: The mass volume ratio of the barium-doped lanthanum cobaltate perovskite catalyst to the wastewater is (0.04-0.08) g: 250 mL.

8. The use according to claim 5, characterized in that: The initial pH value of the wastewater is 5-9.

9. The use according to claim 5, characterized in that: The ozone injection rate is 2-30 mg / min.